2018
DOI: 10.1016/j.ejop.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The affiliation of Hexasterias problematica and Halodinium verrucatum sp. nov. to ciliate cysts based on molecular phylogeny and cyst wall composition

Abstract: Species in the genera Hexasterias and Halodinium have been recorded over the last decades as acritarchs in palynological and/or plankton studies. In paleoenvironmental studies, these resting stages are often interpreted as indicators of freshwater input. The biological affinity of these genera has never been definitely established. Here, a new species, Halodinium verrucatum sp. nov., is described and molecular evidence (single specimen SSU and LSU rDNA sequencing) reveals that both this new species and Hexaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 81 publications
1
19
0
Order By: Relevance
“…Concentrations of organic linings of foraminifera are high in the inner part of the gulf, reaching 2,018 g -1 , with an overall average of 748 linings g -1 . Halodinium sp., described originally as an acritarch (Bujak, 1984) and now confirmed as the resting cyst of an estuarine ciliate (Gurdebeke et al, 2018), are more abundant in the central and southern SJG, with a maximum value of 102 cells g -1 at site BV50, and low concentrations in the northern part of the gulf and offshore. This taxon suggests freshwater inputs to in our study area.…”
Section: Resultsmentioning
confidence: 89%
“…Concentrations of organic linings of foraminifera are high in the inner part of the gulf, reaching 2,018 g -1 , with an overall average of 748 linings g -1 . Halodinium sp., described originally as an acritarch (Bujak, 1984) and now confirmed as the resting cyst of an estuarine ciliate (Gurdebeke et al, 2018), are more abundant in the central and southern SJG, with a maximum value of 102 cells g -1 at site BV50, and low concentrations in the northern part of the gulf and offshore. This taxon suggests freshwater inputs to in our study area.…”
Section: Resultsmentioning
confidence: 89%
“…Most cysts are spherical ( Mulisch and Hausmann, 1989 ; Figures 2 , 3 ) or ellipsoidal ( Foissner et al, 2002 ), although flask-shape ( Kim and Taniguchi, 1995 ) or disk-shaped ( Gurdebeke et al, 2018 ) cysts have also been observed in several species. The size of cysts ranges from 15 μm in Pseudocohnilembus pusillus ( Olendzenski, 1999 ) to 225 μm in Blepharisma japonicum ( Giese, 1973 ).…”
Section: Structure Of Cystsmentioning
confidence: 99%
“…Phylogenetic analyses of SSU rDNA sequences revealed that all investigated strains of Urotricha formed a highly supported monophyletic group together with Plagiocampa sp. (KY980324; Zhang et al, 2014) and Halodinium verrucatum (LC424401; Gurdebeke et al, 2018), which is placed in a distinct clade. Hence, the identification of the latter two sequences is incorrect or the genus Urotricha is not monophyletic.…”
Section: Molecular Phylogeny Of the Genus Urotrichamentioning
confidence: 99%
“…In the SSU rDNA tree of the prostomatids, two Urotricha-related sequences differ morphologically, i.e., Plagiocampa sp. (KY980324; Zhang et al, 2014) and H. verrucatum (LC424401;Gurdebeke et al, 2018). They probably represent misidentifications or crosscontaminations, especially as both the phylogenetic placement and the signatures of the V4 and the V9 gene regions indicate that they are urotrichs (Figures 6, 9).…”
Section: Molecular Markers and Morphology -Indispensable Requirements...mentioning
confidence: 99%